The global spread of crop pests and pathogens. Issue 12 (27th August 2014) - Bebber, Daniel P.; Holmes, Timothy; Gurr, Sarah J.
Abstract Aim To describe the patterns and trends in the spread of crop pests and pathogens around the world, and determine the socioeconomic, environmental and biological factors underlying the rate and degree of redistribution of crop‐destroying organisms. Location Global. Methods Current country‐ and state‐level distributions of 1901 pests and pathogens and historical observation dates for 424 species were compared with potential distributions based upon distributions of host crops. The degree of 'saturation', i.e. the fraction of the potential distribution occupied, was related to pest type, host range, crop production, climate and socioeconomic variables using linear models. Results More than one‐tenth of all pests have reached more than half the countries that grow their hosts. If current trends continue, many important crop‐producing countries will be fully saturated with pests by the middle of the century. While dispersal increases with host range overall, fungi have the narrowest host range but are the most widely dispersed group. The global dispersal of some pests has been rapid, but pest assemblages remain strongly regionalized and follow the distributions of their hosts. Pest assemblages are significantly correlated with socioeconomics, climate and latitude. Tropical staple crops, with restricted latitudinal ranges, tend to be more saturated with pests and pathogens than temperate staples with broad latitudinal ranges. We list the pests likely to be the most invasive in coming years. Main conclusions Despite ongoing dispersal of crop pests and pathogens, the degree of biotic homogenization of the globe remains moderate and regionally constrained, but is growing. Fungal pathogens lead the global invasion of agriculture, despite their more restricted host range. Climate change is likely to influence future distributions. Improved surveillance would reveal greater levels of invasion, particularly in developing countries.